1999
DOI: 10.1086/314716
|View full text |Cite
|
Sign up to set email alerts
|

Excretion into Bile of a Novel Unenveloped DNA Virus (TT Virus) Associated with Acute and Chronic Non‐A–G Hepatitis

Abstract: Recently, an unenveloped, single-stranded DNA virus named TT virus (TTV) has been reported in association with hepatitis of non-A-G etiology. Five patients with TTV viremia, who received bile drainage or cholecystectomy, were tested for TTV DNA in bile by polymerase chain reaction with heminested primers. TTV DNA was detected in bile from all patients; titers were 10-100 times higher than in serum in 4 and at a comparable level in the remaining 1 patient. TTV DNA was detected in feces, also, in 1 of the 2 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 15 publications
7
69
2
1
Order By: Relevance
“…Previous reports have suggested a fecal-oral route of transmission for TTV. 25,26 It is unclear whether TTV is efficiently transmitted by sexual intercourse but recent data obtained in France suggest that this is the case. 42 Most studies on TTV in North America and Europe have shown no significant impact of TTV on liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have suggested a fecal-oral route of transmission for TTV. 25,26 It is unclear whether TTV is efficiently transmitted by sexual intercourse but recent data obtained in France suggest that this is the case. 42 Most studies on TTV in North America and Europe have shown no significant impact of TTV on liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…The route of TTV transmission is also unclear, although there is strong evidence for blood transmission and some studies have suggested a fecal-oral route. 25,26 A few studies have reported a high prevalence of GBV-C/HGV [27][28][29] and TTV infection 30 in sub-Saharan Africa. The prevalence of both types of viral infection within a single African geographical area has not been considered, and the modes of transmission of these viruses in Africa have remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The buoyant density in cesium chloride was found to be 1.31-1.33 g/cm 3 for TTV in serum and 1.33-1.35 g/cm 3 for TTV in feces [2]. Resistance to treatment with detergents, solvents, and dry heat confirmed the absence of a lipid envelope [37,38]. TTV proteins have not been well characterized yet; however, similar to CAV, it is believed that the capsid is made up of a single structural protein.…”
Section: Structure and Genomic Organization Of Ttvmentioning
confidence: 92%
“…Meanwhile, different studies suggested that TTV genotypes were so much and could vary frequently [4][5][6][7][8] . It is believed that TTV belongs to hepadnavirus and replicates chiefly in the liver [9][10][11] , however, some researchers think that the replication site is in the bone marrows rather than in the livers [12] . At present, epidemiological studies suggest that TTV is mainly transmitted by blood [13][14][15] ; blood products [16] and body fluid routes [13,17] , it can also be transmitted by mother-to-child vertical [18] and horizontal [19,20] route , fecal-oral route [9,15,21] and sexual route [22] .…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that TTV belongs to hepadnavirus and replicates chiefly in the liver [9][10][11] , however, some researchers think that the replication site is in the bone marrows rather than in the livers [12] . At present, epidemiological studies suggest that TTV is mainly transmitted by blood [13][14][15] ; blood products [16] and body fluid routes [13,17] , it can also be transmitted by mother-to-child vertical [18] and horizontal [19,20] route , fecal-oral route [9,15,21] and sexual route [22] . The infection rate of TTV DNA varies largely in healthy population and patients with liver diseases, but generally, it is higher in patients than in healthy donors [7,[23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%